Current Topics from the Revised German S2k Guideline on Diagnosis and Treatment of Venous Thromboembolism - Linnemann, Birgit; Klamroth, Robert (Hämostaseologie, 2024)
It is an honor and a great pleasure for us to be guest editors for this special issue of Hämostaseologie – Progress in Haemostasis, which addresses important issues surrounding the complex of venous thromboembolism (VTE). In February 2023, the revised guideline on “Diagnostics and Therapy of Venous Thrombosis and Pulmonary Embolism” has been published on the website of the Association of the Scientific Medical Societies in Germany (AWMF)1. This guideline was drawn up under the leadership of the German Society of Angiology (DGA), and representatives of 17 scientific societies contributed to its content. As an S2k guideline, its recommendations are consensus based and are the result of a systematic review and evaluation of current evidence and consideration of the benefits and harms of diagnostic and therapeutic options. In this special issue, guideline authors provide a comprehensive overview of selected guideline topics which might be of clinical relevance to our readers and our community of haemostaseologists.